Algorithms for sensor systems : 14th International Symposium on Algorithms and Experiments for Wireless Sensor Networks, ALGOSENSORS 2018, Helsinki, Finland, August 23-24, 2018, Revised selected papers /: 14th International Symposium on Algorithms and Experiments for Wireless Sensor Networks, ALGOSENSORS 2018, Helsinki, Finland, August 23-24, 2018, Revised selected papers. (2019) - Unknown
No abstract available